Creative software crowdsourcing: from components and algorithm development to project concept formations. (1st January 2013) - Wu, Wenjun; Tsai, Wei-Tek; Li, Wei
Software development is complex and creative as it involves requirement analysis, design, architecture, coding and testing. Recently, software crowdsourcing has been popular with numerous software coders participated in various software competitions. This paper first analyses the data collected on software crowdsourcing and summarises major lessons learned. This paper then examines two software crowdsourcing processes including TopCoder and AppStori processes. Lastly, this paper identifies the min-max nature among participants as an important design element in software crowdsourcing for software quality and creativity. Although in a min-max game, one party tries to maximise the finding of bugs in a set of artefacts, and the other parties try to minimise the potential bugs in the same artefact, software crowdsourcing can still be a collaborative and win-win process for all parties. By using this approach, lots of aspects of software development can be crowdsourced with the crowd can contribute their creativity to each aspect.